Mixing at the extratropical tropopause as characterized by collocated airborne H2O and O3 lidar observations - Schäfler, Andreas; Fix, Andreas; Wirth, Martin (Atmospheric Chemistry and Physics, 2021)
The composition of the extratropical transition layer (ExTL), which is the transition zone between the stratosphere and the troposphere in the midlatitudes, largely depends on dynamical processes fostering the exchange of air masses. The Wave-driven ISentropic Exchange (WISE) field campaign in 2017 aimed for a better characterization of the ExTL in relation to the dynamic situation. This study investigates the potential of the first-ever collocated airborne lidar observations of ozone (O3) and water vapor (H2O) across the tropopause to depict the complex trace gas distributions and mixing in the ExTL. A case study of a perpendicular jet stream crossing with a coinciding strongly sloping tropopause is presented that was observed during a research flight over the North Atlantic on 1 October 2017. The collocated and range-resolved lidar data that are applied to established tracer–tracer (T–T) space diagnostics prove to be suitable to identify the ExTL and to reveal distinct mixing regimes that enabled a subdivision of mixed and tropospheric air. A back projection of this information to geometrical space shows remarkably coherent structures of these air mass classes along the cross section. This represents the first almost complete observation-based two-dimensional (2D) illustration of the shape and composition of the ExTL and a confirmation of established conceptual models. The trace gas distributions that represent typical H2O and O3 values for the season reveal tropospheric transport pathways from the tropics and extratropics that have influenced the ExTL. Although the combined view of T–T and geometrical space does not inform about the process, location and time of the mixing event, it gives insight into the formation and interpretation of mixing lines. A mixing factor diagnostic and a consideration of data subsets show that recent quasi-instantaneous isentropic mixing processes impacted the ExTL above and below the jet stream which is a confirmation of the well-established concept of turbulence-induced mixing ...